Drones and responsibility: legal, philosophical, and sociotechnical perspectives on remotely controlled weapons - Di Nucci, Ezio; Santoni de Sio, Filippo (Emerging technologies, ethics and international affairs, 2016)
Introduction / Filippo Santoni de Sio & Ezio Di Nucci -- Autonomous drones and individual criminal responsibility / Dan Saxon -- State and individual responsibility for targeted killings by drones / Chantal Meloni -- Autonomous killer robots are probably good news / Vincent C. Müller -- Moral identity and remote controlled killing : a missing perspective / Bernhard Koch -- State responsibility and drone operators / Jesse Kirkpatrick -- The threshold of killing drones : the modular turing imitation game / Asa Kasher -- Delegation and responsibility : a human-machine perspective / Tjerk de Greef -- Civilizing drones by design / Aimee van Wynsberghe & Michael Nagenborg -- Drones, automated targeting, and moral responsibility / Alex Leveringhaus -- Drones combat : enhanced information warfare and three moral claims of combat drone responsibility / Michael Funk, Bernhard Irrgang & Silvio Leuteritz -- Autonomous killer drones / Nikil Mukerji